Waste management transformation with black soldier fly maggot and ecobrick at SMP Negeri 3 Sewon based on Pancasila Project - Fitria Sulistyowati; Devi Septiani; Ika Wahyu Kusuma Wati; Sony Yunior Erlangga; Tyas Susilowati; Wulan Rahmawati; Anisa Putri Damayanti; Okky Lupitasari Widianingrum; Khansa Amalia Ayona (Community Empowerment, 2024)
Daily waste production in the Yogyakarta Special Region, exceeding 1,000 tons, threatens community health and quality of life. The Yogyakarta Special Region Governor prioritizes waste reduction, including in educational institutions. The Merdeka Curriculum, with its P5 Project, encourages interactive learning and practical waste management, making it highly relevant for increasing students' awareness. This community service program aims to assist in implementing P5 Projects focused on waste management using Black Soldier Fly (BSF) maggots and ecobricks to reduce waste at its source. Methods include socialization, training, technology application, and ongoing support. Results demonstrate program success: 100% of teachers understand organic and inorganic waste management and are prepared to teach students; 100% of teachers implemented a complete cycle of the P5 Project using BSF maggots and ecobricks; two cross-generational P5 Project teams formed with defined responsibilities; and the implementation of a PPEPP system ensures the program's structured and sustainable continuation.